(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Onishchenko I.V. Information and communication pedagogical environment of modern higher educational institution as means of forming future specialists’ professionalism. Basing on systematic structural analysis, the article deals with the theoretical and the methodological problems of forming information and communication pedagogical environment of modern higher educational institution, features of its influence on the education system and on improving the quality of specialists’ training.